Cities and innovations in Europe challenges and visions - MEGA, Voula (European Spatial Research and Policy, 1995)
The paper presents the first results of the European Overview of Urban lnnovations, undertaken by the European Foundation for the Improvemenl of Living and Working Conditions. The identified projects have been chosen from among projects which improve the urban metabolism, carry a collective sense, resis1 time, favour !ocal democracy and participation at the conception, decision and execution phases, produce culture and projects whose models are transferable to different places, respecting the difference. Projects concemed with urban environmental auditing or favouring social justice in cities are extremely important as they lead to a new art of planning for the achievement of the European sustainable city.